2015
DOI: 10.1038/nchem.2306
|View full text |Cite
|
Sign up to set email alerts
|

Significantly shorter Fe–S bond in cytochrome P450-I is consistent with greater reactivity relative to chloroperoxidase

Abstract: Cytochrome P450 (P450) and chloroperoxidase (CPO) are thiolate ligated heme proteins that catalyze the activation of carbon hydrogen bonds. The principal intermediate in these reactions is a ferryl radical species called compound I. P450 compound I (P450-I) is significantly more reactive than CPO-I, which only cleaves activated C-H bonds. To provide insight into the differing reactivities of these intermediates, we examined CPO-I and P450-I with variable temperature Mössbauer and X-ray absorption spectroscopie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
96
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 49 publications
15
96
1
Order By: Relevance
“…The comparison of these data extracted from fragment, D Fe=O and E Fe=O , and spin-orbit free (J SF ) calculations, with those extracted from the full complex including spin-orbit coupling shows that there is only a small deviation between the two approaches and that the model Hamiltonian accurately describes the magnetic properties. The calculations predict a |J SF | value 30%(BS) and 40%(DDCI) larger in o than in p, in agreement with the |J| relation between P450-I and CPO-I obtained by Krest and co-workers [272]. As most salient details, we observe that the spin-orbit coupling slightly enhances the isotropic coupling and that the simultaneous description of all three electrons levels o↵ the variation of the axial anisotropy with the Fe-S distance.…”
Section: Universitat Rovira I Virgili From Mononuclear To Dinuclear: supporting
confidence: 75%
See 2 more Smart Citations
“…The comparison of these data extracted from fragment, D Fe=O and E Fe=O , and spin-orbit free (J SF ) calculations, with those extracted from the full complex including spin-orbit coupling shows that there is only a small deviation between the two approaches and that the model Hamiltonian accurately describes the magnetic properties. The calculations predict a |J SF | value 30%(BS) and 40%(DDCI) larger in o than in p, in agreement with the |J| relation between P450-I and CPO-I obtained by Krest and co-workers [272]. As most salient details, we observe that the spin-orbit coupling slightly enhances the isotropic coupling and that the simultaneous description of all three electrons levels o↵ the variation of the axial anisotropy with the Fe-S distance.…”
Section: Universitat Rovira I Virgili From Mononuclear To Dinuclear: supporting
confidence: 75%
“…Being directly associated with the axial coordination of the metal, these di↵erences are expected to have a significant e↵ect on the reactivity. Recently, Green and co-workers have suggested that the larger reactivity of the cytochrome P450-I as compared to CPO-I is related to the shorter Fe-S distance in the former [272]. The larger exchange splitting -proportional to the energy di↵erence of the doublet and quartet spin state (see below )-of P450-I was suggested to be an indication of higher spin density on sulphur with respect to the CPO-I analogue.…”
Section: Universitat Rovira I Virgili From Mononuclear To Dinuclear: mentioning
confidence: 99%
See 1 more Smart Citation
“…If the mutation had no effect on the intrinsic reactivity of Cpd I, then the mutation-induced decrease in the rate of cryo-conversion of the hydroperoxy intermediate into Cpd I would be expected to decrease the rate but not yield of product formation during relaxation of cryoreduced oxy ferrous P4502B4. Thus, the observed ∼ 4% cryo-yield of BHTOH for the F429 H mutant, compared to wt product cryo-yield of approximately 80%, may be explained by strongly diminished intrinsic reactivity of the Cpd I active species, which in turn results in an increased destruction of Cpd I through side reactions of Cpd I with radiolytically generated radicals 53,29 In support of this view, it is worth noting that the D251N mutation in P450cam, which slows the rate of hydroxylation of camphor at ambient temperatures, has no effect on the yield of product during annealing the cryoreduced ternary oxy P450cam-camphor complex 28 .…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown recently that the low reactivity of Cpd I of CPO relative to that of P450s correlates with a lengthening in the Fe-S distance caused by the additional H-bond to axial thiolate in CPO. 28 Functionally, the F429H mutation was shown to substantially slow the rate of autooxidation of oxy ferrous P4502B4 complex, and to decrease the activity by over 90%. 19 …”
mentioning
confidence: 99%